Evidence that KARRIKIN-INSENSITIVE2 (KAI2) Receptors may Perceive an Unknown Signal that is not Karrikin or Strigolactone - Conn, Caitlin E.; Nelson, David C. (Frontiers in Plant Science, 2016)
The α/β-hydrolases KAI2 and D14 are paralogous receptors for karrikins and strigolactones, two classes of plant growth regulators with butenolide moieties. KAI2 and D14 act in parallel signaling pathways that share a requirement for the F-box protein MAX2, but produce distinct growth responses by targeting different members of the SMAX1-LIKE/D53 family. kai2 and max2 mutants share seed germination, seedling growth, leaf shape, and petiole orientation phenotypes that are not found in d14 or SL-deficient mutants. This implies that KAI2 recognizes an unknown, endogenous signal, herein termed KAI2 ligand (KL). Recent studies of ligand-specificity among KAI2 paralogs in basal land plants and root parasitic plants suggest that karrikin and strigolactone perception are evolutionary adaptations of KL receptors. Here we demonstrate that evolutionarily conserved KAI2c genes from two parasite species rescue multiple phenotypes of the Arabidopsis kai2 mutant, unlike karrikin- and strigolactone-specific KAI2 paralogs. We hypothesize that KAI2c proteins recognize KL, which could be an undiscovered hormone.